Analisis Kinematik Singularty Pada Manipulator 7 DOF Dengan Software Simulasi ROBOAnalyzer - Nur Akhlis Sarihidaya Laksana; Radhi Ariawan; Unggul Satria Jati; Jenal Sodikin; Ulikaryani (P3M Politeknik Negeri Cilacap, 2022)
Studies related to manipulators are still being carried out, along with the times and needs. Utilization in manufacturing and fabrication has led to the development of many manipulators. Smooth, fast, and accurate movement continue to be developed. In the case of the multi manipulator, 7 DOF (Degree of Freedom) is a type of manipulator that has special features in terms of joints. Inverse kinematic is a parameter used to control the orientation and movement of the manipulator. 7 DOF has three singularity wrist, elbow, and shoulder. In the simulation, each singularity produces an inverse kinematic matrix which is used to control the movement of the manipulator. The method used is to determine the angle of motion of the joint (continues joint angel) with simulation to produce calculations that are fast, precise, accurate, and stable. The target of each joint with the theta value that has been determined by the singularity was successfully carried out with an error of 0%.